Interfacing of biped KHR-1 with DSP board TMS320F2812 - Lim, Chot Hun; Wong, Eng Kiong; Koo, Voon Chet (2006)
This paper describes the interfacing of the biped robot KHR-1 with DSP board TMS320F2812. In this study, the KHR-1 is modeled as a seven-link biped, with each joint connected with a servomotor KRS-784 ICS. The I/O port of the DSP board provides PWM signals to the biped joints for joint control. TMS320F2812 is chosen due to its high PWM resolution as well as its flexibility in PWM frequency setting. The computed joint trajectories of the biped robot are based on the Zero Moment Point (ZMP) model. Walking trajectories are constructed and tested, and the results are beneficial to both biped research as well as mechatronics education for undergraduates.